Self-Management Strategy of Students in Facing Fomo Challenges and Increasing Social Media Involvement in Islamic Boarding School - Mirawati; Heru Kurnianto Tjahjono; Tasman Hamami; Fitriah M. Suud (Nazhruna: Jurnal Pendidikan Islam, 2025)
Technological advances bring new challenges for receptionists, such as Fear of Missing Out (FOMO) and high social media engagement. This study aims to explore self-management strategies in dealing with FOMO challenges and increasing healthy social media engagement in the dormitory environment. This study uses a qualitative approach with in-depth interviews with 6 students who are included in the respondent criteria from the Strensains Islamic boarding school in the Sragen area. Data analysis was carried out using the NVIVO12 application and data use was carried out using the interactive data analysis model from Miles which consists of three stages, namely: coding, data reduction, data presentation and finally drawing conclusions. The results of the study indicate that students develop various effective self-management strategies. First, students try to maintain daily routines in training, such as worship, study, and other activities. Second, students limit the use of exercise and social media, which are the main sources of exposure to content that triggers FOMO. Third, students develop interests and hobbies outside of social media, such as sports, arts, or extracurricular activities. The findings of the study contribute to a more comprehensive understanding of the psychological dynamics of students in dealing with digital challenges. The identified self-management strategies can be a model for other centers in managing social media use and preventing the negative impacts of FOMO. This study also provides practical implications for nurses in nursing homes in designing training programs that support centers in using social media wisely and enhancing healthy social engagement in the training environment.